STRENGTHENING THE COMPETENCE OF JUNIOR HIGH SCHOOL EXTRACURRICULAR COACHES THROUGH MULTI-SPORT PHYSICAL CONDITION TRAINING COACHING CLINICS - Puriana, Ramadhany Hananto; Wahyono , Muhammad; Kusuma, Angga Indra; Muhammad; Mbabho, Finsensius (Antis-publisher, 2026)
Objective: This community service activity aimed to strengthen the competence of junior high school extracurricular coaches through a coaching clinic focused on physical conditioning training across multiple sports. The program addressed the limited ability of school coaches to design structured and scientifically based physical training programs. Method: The activity employed a participatory training approach using a coaching clinic model involving interactive lectures, demonstrations, direct practice, and reflective discussions. Participants consisted of extracurricular sports coaches from various disciplines. The program was implemented in three stages: preparation, implementation, and evaluation. Data were collected through pretest–posttest assessments and evaluation of training program designs developed by participants. Results: The findings indicated a significant improvement in participants’ understanding and practical skills. The average score increased from 60.7 (pretest) to 83.9 (posttest), with an overall improvement of 38.2%. Participants were able to develop more structured, systematic, and applicable physical training programs. Additionally, active engagement and positive responses were observed throughout the activity, indicating the effectiveness of the coaching clinic approach. Novelty: This program offers a practical and integrative coaching clinic model specifically designed for multicategory sports coaches at the school level. It bridges the gap between theoretical knowledge and field application by emphasizing hands-on experience and contextual learning, which is rarely addressed in conventional coach training programs.